2015
DOI: 10.1007/s10916-015-0413-1
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Estimation of Osteoporotic Fracture Cases by Using Ensemble Learning Approaches

Abstract: Ensemble learning methods are one of the most powerful tools for the pattern classification problems. In this paper, the effects of ensemble learning methods and some physical bone densitometry parameters on osteoporotic fracture detection were investigated. Six feature set models were constructed including different physical parameters and they fed into the ensemble classifiers as input features. As ensemble learning techniques, bagging, gradient boosting and random subspace (RSM) were used. Instance based le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
0
13
0
2
Order By: Relevance
“…( 42,52 ) As outcome, studies classified osteoporotic versus normal patients, ( 29,36,39,40,43,49,50,52,54–57,62 ) osteoporotic versus non‐osteoporotic patients (based on a BMD T ‐score threshold of –2.5 SD), ( 34,38,44,64 ) normal versus abnormal subjects (based on the BMD T ‐score threshold of −1 SD), ( 33,41,42,45,47,48,58–60,65 ) experimented multiple classifications, ( 46,63 ) or assigned to three classes: osteoporosis (BMD T ‐score ≤ −2.5 SD), osteopenia (−2.5 < BMD T ‐score ≤ −1), and normal (BMD T ‐score > −1 SD). ( 32,37,51,61 ) The models were internally validated in almost each study, and in two of them the models were also externally validated. ( 32,50 ) Twelve studies validated their model using accuracy with an average performance of 90.1% (range 70.0% to 98.9%); 22 validated their model using AUC with a mean of 0.90 (range 0.74 to 1.00).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…( 42,52 ) As outcome, studies classified osteoporotic versus normal patients, ( 29,36,39,40,43,49,50,52,54–57,62 ) osteoporotic versus non‐osteoporotic patients (based on a BMD T ‐score threshold of –2.5 SD), ( 34,38,44,64 ) normal versus abnormal subjects (based on the BMD T ‐score threshold of −1 SD), ( 33,41,42,45,47,48,58–60,65 ) experimented multiple classifications, ( 46,63 ) or assigned to three classes: osteoporosis (BMD T ‐score ≤ −2.5 SD), osteopenia (−2.5 < BMD T ‐score ≤ −1), and normal (BMD T ‐score > −1 SD). ( 32,37,51,61 ) The models were internally validated in almost each study, and in two of them the models were also externally validated. ( 32,50 ) Twelve studies validated their model using accuracy with an average performance of 90.1% (range 70.0% to 98.9%); 22 validated their model using AUC with a mean of 0.90 (range 0.74 to 1.00).…”
Section: Resultsmentioning
confidence: 99%
“…( 29,32–34,36–65 ) Osteoporosis classification was made based on lumbar BMD, ( 32–34,37,51 ) hip BMD, ( 38,50,58 ) lumbar and hip BMD, ( 29,39–42,46–48,53,59,60 ) other non‐standard assessments, ( 43,44,49,54–56,65 ) or unspecified. ( 36,45,52,57,61–64 ) Studies identified osteoporosis based on opportunistic imaging from CT, ( 32–34 ) X‐ray, ( 37,38,43–45,55–59,63,64 ) or dental imaging; (36,47–49,53,54,60,62 ) other studies used data from patient characteristics, ( 40,41,50,51,61,65 ) bone biomarkers, (29,39 ) or acoustical responses. ( 42,52 ) As outcome, studies classified osteoporotic versus normal patients, ( 29,36,39,40,43,49,50,52,54–57,62 ) osteoporotic versus non‐osteoporotic patients (based on a BMD T ‐score threshold of –2.5 SD), ( 34,38,44,64 ) normal versus abnormal subjects (based on the BMD T ‐score threshold of −1 SD), ( 33,41,42,45,47,48,58–60,65 ) experimented multiple classifications, ( 46,63 ) or assigned to three classes: osteoporosis (BMD T ‐score ≤ −2.5 SD), osteopenia (−2.5 < BMD T ‐score ≤ −1), and normal (BMD T ‐score > −1 SD).…”
Section: Resultsmentioning
confidence: 99%
“…Los algoritmos que se van a evaluar son los siguientes: Forest PA [23], J48 [24], Random Forest [14], EBMC [25], TAN, NB Tree [25], DTNB [26], FURIA [27] y Classification VIa Regression, que son algoritmos populares en el campo de la clasificación de datos de salud.…”
Section: ) Minería De Datosunclassified
“…Las técnicas de clasificadores toman los datos de cada paciente y predicen la presencia de enfermedades basadas en patrones subyacentes. Las máquinas de vectores de soporte (MVS) [13], los random forest (RF) [14] y las redes neuronales artificiales (RNA) [15] han sido enfoques ampliamente utilizados en el aprendizaje automático [2].…”
Section: Introductionunclassified
“…Osteoporotic vertebral fracture is occurred due to bone-osteoporosis in which vertebral bones are shirked as the bone mass is lowered. In vertebral osteoporosis, bones become narrow and weaken with osteoporosis that causes the fracture [8]. Statistics reveal that approximately eight point nine million fractures of vertebral column are caused due to osteoporosis on annual basis, which means that osteoporotic vertebral fracture is caused after every three seconds worldwide [9].…”
Section: Introductionmentioning
confidence: 99%